Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

How competition shapes energy efficiency in shared e-scooter systems - Yuhan Zhang; Jiaming Wu; Zhirui Ye; Maria Attard (Transportation Research Part D: Transport and Environment, 2026)

SMOTE-DNN algorithm for accurate recognition and classification of VAHs with minimal dataset requirements - Zijian Zhang; Jiaming Li; Wu Wang; Zhengmao Cao; Qingqing Ye; Chenyu Du; Ye He; Yanjuan Sun; Behzad Rezaei; Jianping Sheng; Fan Dong (Environmental Research, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

P300-mediated H3K56la delactylation promotes copper-induced steroidogenesis disorders in human ovarian granulosa cells - Panlin Wang; Jiaming Xiao; Bingbing Wang; Yi Zhang; Ke Xu; Yingjie Dou; Qianqian Guo; Ye He; Yan Sun; Wenxiang Wang (Journal of Hazardous Materials, 2026)

3D mechanical stimulation modulates endothelial exosomes to promote fibroblast activation - Ye Qiu; Zhenkun Lv; Xingying Zhu; Xiaoqian Yang; Jiaming Wan (Tissue and Cell, 2026)

High turbidity induced by extreme precipitation complicates the relationships between molecular and optical properties of DOM in the Yangtze River - Yue Ren; Guangrui Yang; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (Journal of Water Process Engineering, 2026)

QACO: An adaptive multi-phase ant colony optimization approach for robust feature selection - Zihang Wang; Ye Liang; Wenwei Sun; Jiaming Liu (Swarm and Evolutionary Computation, 2026)

Targeting argH to attenuate Aeromonas dhakensis virulence: A metabolic checkpoint for biofilm formation and stress adaptation - Xueqian Wang; Chenlu Yang; Xuesong Li; Wei Feng; Jianguo Zhao; Yukun Wu; Shuai Ye; Meng Zhao; Hanzeng Li; Jiaming Ju; Guiying Guo; Lixia Fan; et al. (Veterinary Microbiology, 2025)

Reshaping spatial–temporal pattern of suspended sediment concentration in the Yangtze River mainstem by damming reservoirs based on nearly 40 years Landsat observations - Farong Chen; Guangrui Yang; Yanhui Dai; Jiale Jin; Chu Zhao; Zhishan Ye; Jiaming Chen; Xinyi Zhang; Tao Huang; Changchun Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Porcine liver peptide ameliorates ethanol-induced liver injury via the NQO1 and ACAA1 signaling pathway through regulating oxidative stress and lipid metabolism - Zixu Wang; Lujuan Xing; Jingyu Wang; Jiaming Cai; Yuejing Hao; Ye Tao; Wangang Zhang (Food Bioscience, 2025)

Developing the chemistry module for 27 fluorinated greenhouse gases (F-gases): Reactions, emissions, and implementation in GEOS-Chem - Yali Li; Lei Zhu; Juan Li; Yuyang Chen; Luke M. Western; Dickon Young; Jens Mühle; Ray F. Weiss; Paul B. Krummel; Chris R. Lunder; Song Liu; Xicheng Li; et al. (Atmospheric Environment, 2025)

A performance improving method of preparing nonlinear conductive coating for HVDC insulator based on plasma treatment technology: For lower-additive amounts and higher adhesive stability - Zijun Pan; Jiaming Cheng; Quanyou Nie; Zirui Wu; Yujie Qiu; Yuhan Ye; Shiyi Mao; Pu Han; Cheng Pan; Ju Tang (Chemical Engineering Journal, 2025)

An in-situ generated multiphase catalyst for active and durable ammonia protonic ceramic fuel cells - Haiyang Lan; Zixuan Xue; Jiakun Sun; Jiaming Chu; Jiangyuan Feng; Weitao Jin; Zixian Wang; Ruiqing Song; Pengfei Yan; Liang Zhang; Yucun Zhou; Xiaofeng Ye; et al. (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Genome-wide identification of the SmPHR gene family in Salvia miltiorrhiza and SmPHR7-mediated response to phosphate starvation in Arabidopsis thaliana - Xinxin Wang; Renjun Qu; Shiwei Wang; Jiaming Peng; Juan Guo; Guanghong Cui; Tong Chen; Meilan Chen; Ye Shen (Plant Cell Reports, 2025)

Fabrication and saltiness enhancement of salt hollow particles by interface migration - Kailin Ye; Jiafeng Chen; Xinyu Zhang; Jiaming Qi; Zihan Qin; Jinmei Wang (Food Research International, 2025)

Ecological and Evolutionary Factors Contribute to the Uneven Diversification of Firs in the Northern Hemisphere - Qiaoping Xiang; Jie Yang; David S. Gernandt; Tongxin Ye; Ling Yang; Jiaming Pan; Ruichen Xiang; Cheng Zhao; Koh Nakamura; Xianchun Zhang; Yongbo Liu; Ran Wei (Journal of Biogeography, 2025)
Aim The Northern Hemisphere harbours the greatest diversity of temperate plants on Earth, with East Asia having the highest species richness compared with North America and Europe. When and how this uneven diversification pattern emerged remains unclear. Here, we use a conifer genus that forms extensive forests in the Northern Hemisphere to explore a fundamental question in ecology and evolution: what processes underlie temperate biodiversity through time and space? Location The Northern Hemisphere. Taxon Abies . Methods To reconstruct a well‐supported framework for estimating diversification rate, we performed phylogenetic analyses using concatenation and coalescent methods based on 58 fir taxa and 56 nuclear single‐copy genes. Niche evolution was explored using species occurrence data and environmental factors based on the l1ou model. Multiple regression was carried out to identify correlations between species richness and environmental variables at global and regional scales, to evaluate factors of species diversity preference, and potentially to explain the evolutionary history of firs. Results We identified East Asia as having the highest species diversity and speciation rate. Two clade‐specific niche shifts corresponding with the distribution of firs were detected, one in the Himalaya‐Hengduan Mountains ( c. 12.2 Ma) and the other in the Mexican highlands ( c. 14.3 Ma), but none in the Euro‐Mediterranean region. Fir species richness increased with cool temperatures both globally and regionally. Seasonal precipitation showed significant positive correlation to species richness on a global scale and in North America and the Euro‐Mediterranean region. Soil factors showed significant trends and moderate correlations with species richness in the Himalaya‐Hengduan Mountains and Mexican highlands. Main Conclusions Our results indicate that modern firs prefer cool climates with seasonal rainfall. East Asian firs experienced niche shifts with the Himalayan orogeny in the Middle Miocene. Novel heterogeneous habitats due to changes in topography and the establishment of a monsoon climate, accompanied by niche shift, can account for the high speciation of firs in East Asia. A similar process is found in the Mexican highland firs. In contrast, cold–dry continental climate in North America since the late Paleogene and the lack of seasonal rainfall and relatively stable topography in the Euro‐Mediterranean region are the main limiting factors for fir diversification. Our study rejects the ‘clade age’ hypothesis but supports the hypothesis that niche shift related to high diversification rate triggered by environmental heterogeneity underlies the uneven species diversity of the Northern Hemisphere.

Cell wall and reactive oxygen metabolism responses of stored Shine Muscat grapes to combined melatonin and 24-epibrassinolide treatment - Yaoying Zeng; Jiaming Zhang; Hui Su; Le Xie; Ye Zhao; Yubo Xiong; Zhou Wenhua (Postharvest Biology and Technology, 2025)

Effect of heat treatment on the stability of ultrasound-assisted cross-linked myofibrillar protein-stabilized emulsion filler phases via rheology and tribology - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Qi Wang; Zhen Li; Jingyu Wang; Xinglian Xu (Food Hydrocolloids, 2025)

Influence of staggered guide vane on hydraulic performance of reactor coolant pump - Binhao Liu; Daoxing Ye; Junlin Chen; Mengke Wu; Rui Deng; Junyu Zhang; Jiaming Han (Annals of Nuclear Energy, 2024)

Application of rheology and interfacial rheology to investigate the emulsion stability of ultrasound-assisted cross-linked myofibrillar protein: Effects of oil phase types - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Weiyi Zhang; Xinglian Xu (Food Hydrocolloids, 2024)

Effect of Yamadazyma triangularis derived peptide XHY69AP on muscle fatigue via regulation of AMPK/PGC-1α and Nrf2/Keap1 pathways - Jiaming Cai; Ye Tao; Lujuan Xing; Lei Zhou; Ming Ju; Wangang Zhang (Food Bioscience, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

High-efficient photocatalytic degradation of multiple pollutants by CdPS3 nanosheets - Bingda Li; Jiaming Song; Yuting Li; Chaoying Meng; Shuxian Wang; Linghao Zong; Honggang Ye; Yishuai Jing; Feng Teng; Peng Hu; Haibo Fan; Guangde Chen; et al. (Process Safety and Environmental Protection, 2024)

Exploring the relationship between the interfacial properties and emulsion properties of ultrasound-assisted cross-linked myofibrillar protein - Ye Tao; Jiaming Cai; Peng Wang; Jiahui Chen; Lei Zhou; Zongyun Yang; Xinglian Xu (Food Hydrocolloids, 2024)

Statistical modeling and dependence analysis for tide level via multivariate extreme value distribution method - Ali Tian; Xufeng Shu; Jiaming Guo; Haoyun Li; Renchuan Ye; Peng Ren (Ocean Engineering, 2023)

Catalytic degradation of bisphenol a (BPA) in water by immobilizing silver-loaded graphene oxide (GO-Ag) in ultrafiltration membrane with finger-like structure - Ye Yang; Fangbo Zhao; Liu Yang; Jiaming Zhang; Hee-Deung Park; Zhiguo Li; Hongxu Chen; Ximeng Zhang; Mingjin Gao (Chemical Engineering Journal, 2023)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Enhancement of sodium salty taste modulate by protease-hydrolyzed Gum Arabic - Kailin Ye; Jiaming Qi; Yang Zhang; Jinmei Wang; Jian Guo; Xiaoquan Yang (Food Hydrocolloids, 2023)

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Correction to: Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Modulating red mud for the fabrication of cementitious material by analyzing the thermal evolution of hydrogarnets - Beibei Wang; Jiaming Wu; Xiaojie Sun; Jun Jiang; Qingchun Yang; Quanliang Li; Zhengmao Ye; Jiayu Guo; Xiaohao Wang (Environmental Science and Pollution Research, 2023)

Systematical site investigation and temperature sensing in Pr3+-doped M3RE4O9 (M = Sr and Ba; RE = Sc, Y, Lu) - Xiangyu Han; Changqing Hu; Jiaming Wu; Shuxian Wang; Zhengmao Ye; Qingchun Yang (Chemical Engineering Journal, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Two new phenolic glycosides with anti-complementary activity from the roots of Sanguisorba officinalis L - Rongshen Wang; Jinfeng Sun; Mei Jin; Chao Ye; Jiaming Wang; Long Jin; Ying Jie Ma; Wei Zhou; Gao Li (Natural Product Research, 2021)

Two novel flavonoids from the leaves of Rhododendron dauricum L. with their inhibition of TNF-α production in LPS-induced RAW 264.7 cells - Chao Ye; Mei Jin; Chunshi Jin; Rongshen Wang; Jiaming Wang; Ying Zhang; Sainan Li; Jinfeng Sun; Wei Zhou; Gao Li (Natural Product Research, 2021)

A new pentacyclic triterpenoid from the leaves of Rhododendron dauricum L. with inhibition of NO production in LPS-induced RAW 264.7 cells - Jiaming Wang; Mei Jin; Chunshi Jin; Chao Ye; Yi Zhou; Rongshen Wang; Huanhuan Cui; Wei Zhou; Gao Li (Natural Product Research, 2020)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)

A new aryldihydronaphthalene-type lignan and other metabolites with potential anti-​inflammatory activities from Corispermum mongolicum Iljin - Yi Zhou; Mei Jin; Chunshi Jin; Chao Ye; Jiaming Wang; Jinfeng Sun; Cheng-Xi Wei; Wei Zhou; Gao Li (Natural Product Research, 2020)